Ethnic-based Online Hate Speech in Ethiopia: Its Typology and Context - Minaye, Abebaw; Megersa, Tadesse (Ethiopian Journal of Social Sciences, 2023)
Using language that devalues others is known to be the royal road to enemy-making, identity based conflict and genocide. Parallel to the explosive growth of social media users in Ethiopia, hate speech has increased to the point where it is threatening the social fabric of its people. The present archival qualitative study presents a conceptual grounded theory to explore and explain the various types of ethnic-based hate speech and the contexts in which they are embedded in present Ethiopia. To this end, data were manually collected every fortnight from July 2021- February 2022, from the public space of ten Facebook accounts, four YouTube news channels, and four Twitter accounts that are purposefully identified as hot spots. By employing inductive coding technique; codes, concepts and categories were generated and analyzed. The findings showed four types of hate speech: dehumanization, enemification, devaluation, and desire to attack and evict as well as five main contexts for the expressions: competition and disagreement over history and resource, the conflict in the North, lack of tolerance of diversity, failure to uphold law and order and destructive roles of the elite. In addition, key concepts are identified which explain how hate speech occurs.  Finally, it is recommend that we should deal with the identified contexts, enhance media literacy and tolerance of diversity and counter toxic intergroup narratives.